Telehealth and Digital Technology: Challenges and Opportunities in Cancer Care - Abdelaleem, Mohamed F. (International Journal of Membrane Science and Technology, 2023)
Telehealth describes the deployment of remote technology as a means to afford healthcare services to individuals who face challenges in accessing adequate healthcare.The efficacy of telemedicine has been well established to be comparable to in-person care, resulting in enhanced accessibility and reduced expenses, while also garnering substantial satisfaction among patients and healthcare providers, particularly in the case of chronic diseases including cancer. This review is conducted to offer a full study of the implementation and utilization of telehealth and digital technology in the oncology practice aiming to explain the updates in trends, barriers, and opportunities in cancer care delivery using digital health.